MODELING THE METHODOLIGICAL ACTIVITY OF TECHNOLOGY EDUCATION TEACHERS - M. Kh. Ikramova; Zahrokhan Makhmitaliyeva; Durdonakhan Olimjonova; Nigora Tursunaliyeva (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, opinions are expressed regarding the modeling of the methodological activity of technology education teachers and their current situation. Education of the young generation requires great responsibility and knowledge from pedagogues. The methodical activity of the teacher is of great importance in the development of science.